2006
DOI: 10.1007/s10517-006-0307-9
|View full text |Cite
|
Sign up to set email alerts
|

Participation of mesenchymal precursor cells in wound healing on skin flap model

Abstract: We studied the state of different pools of mesenchymal precursor cells in the bone marrow, peripheral blood, and wound surface after modeling of tissue damage by skin flap removal. The participation of regional and circulating stromal precursors in the healing of skin defect and the absence of compensatory reaction of the regeneratory process deep reserve, mesenchymal stem cells of the bone marrow, was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Hematopoietic and endothelial progenitors increase transitorily their numbers in PB after a traumatic event. In addition, recent reports suggested that mesenchymal cells would be mobilized in humans after injuries such as wound healing , hip fracture , or cardiac and/or respiratory failure . In this regard, we previously described a similar result in acute skeletal muscle injury in subjects running a long distance race .…”
Section: Discussionsupporting
confidence: 61%
“…Hematopoietic and endothelial progenitors increase transitorily their numbers in PB after a traumatic event. In addition, recent reports suggested that mesenchymal cells would be mobilized in humans after injuries such as wound healing , hip fracture , or cardiac and/or respiratory failure . In this regard, we previously described a similar result in acute skeletal muscle injury in subjects running a long distance race .…”
Section: Discussionsupporting
confidence: 61%
“…Wound healing is still an actual problem of regenerative medicine. The investigation of the processes occurring during the regeneration of skin tissue will open new possibilities for cell therapy [14]. The objective of our study was the investigation of the effect of bone marrow-derived stem cells for the regeneration of skin tissue in BALB/c mouse in a full-thickness wound model.…”
Section: Discussionmentioning
confidence: 99%
“…Step 8: The study of mesenchymal progenitors content in the wound, their functional activity, and production of growth factors by stromal cells from the surface of the wound. Goldberg et al, 2006;Zyuz'kov et al, 2012 Reference (video) Öz et al, 2016;Qureshi et al, 2019 Liability Company Assortiment Firm, Sergiev Posad city, Russia), water ad libitum. To exclude seasonal fluctuations of studied parameters, all the experiments were performed in the autumn-winter period.…”
Section: Methodsmentioning
confidence: 99%
“…The pool of CFU in the S-phase of the cell cycle was determined according to the formula: N = [(a-b)/a] × 100%, where a is the average for the group the number of CFU-F from cells not treated with hydroxyurea; b -the average for the group the number of CFU-F from cells treated with hydroxyurea. The intensity of the processes of specialization of progenitors was determined by calculating the ratio of the corresponding clusterforming (ClFU-F, clusters containing 20-30 cells) to CFU -F (differentiation index) (Goldberg et al, 2006, Zyuz'kov et al, 2012.…”
Section: Study Of Mesenchymal Progenitors Content In the Wound And Their Functional Activitymentioning
confidence: 99%
See 1 more Smart Citation